Protection against phalloidin-induced liver injury by oleanolic acid involves Nrf2 activation and suppression of Oatp1b2. Issue 1 (5th January 2015) - Lu, Yuan-Fu; Liu, Jie; Wu, Kai Connie; Klaassen, Curtis D.
Graphical abstract